Using static-dynamic exercises to improve strength performance in elite Brazilian Jiu-Jitsu athletes - Tropin, Y.; Podrigalo, L.; Romanenko, V.; Kovalenko, Y.; Boychenko, N.; Podrihalo, O.; Volodchenko, O. (Journal of Physical Education and Sport, 2024)
Problem statement: There is a need to assess the effectiveness of integrating static-dynamic exercises into the training routines of elite Brazilian Jiu-Jitsu athletes to enhance their strength performance. This study aims to determine whether such exercises can lead to enhancements in strength, endurance, or other pertinent physical attributes crucial for Brazilian Jiu-Jitsu athletes. The authors aim to address potential gaps in existing training methodologies and advocate for evidence-based strategies to optimize athletic performance in this specific context. The purpose of this study is to examine the impact of static-dynamic exercises on the strength of Brazilian Jiu-Jitsu athletes. Material and Methods: the study involved 20 elite athletes. They were divided into two groups: a control group comprising 10 athletes (age: 20.06±1.02 years; weight: 81.49±3.83 kg; height: 178.5±4.27 cm) and an experimental group comprising 10 athletes (age: 19.97±1.09 years; weight: 81.99±3.55 kg; height: 177.4±3.85 cm). The training program for the experimental group included static-dynamic exercises. Results: at the end of the study, a 50% reliable improvement in results was observed among the athletes in the experimental group: pull-ups for 20 seconds (U=81.0, p<0.05), sit-ups for 20 seconds (U=78.5, p<0.05), pull-ups (U=79.0, p<0.05), push-ups (U=77.0, p<0.05), and bent-arm hang (U=77.5, p<0.05). These tests are indicative of muscle strength in the abdominal and shoulder girdle. Conclusions: the use of static-dynamic exercises has been found to enhance the strength performance of elite Brazilian Jiu-Jitsu athletes. The increase in strength performance results among athletes in the experimental group ranged from 4.5% to 22.0%, while the increase in the control group ranged from 0.5% to 3.2%. It is recommended to incorporate the developed training programs into the preparation of Brazilian Jiu-Jitsu athletes` performance.